Are travellers' perceptions sufficient in evaluating ecotour operator ethics? A case study of Tambopata Reserve, Peru. (17th February 2009) - Nowaczek, Agnes M.K.; Smale, Bryan
Most travellers assume Ecotourism operators embrace ethical practices because they rely on ecological integrity. However, pressures to maintain economic viability raise questions regarding the adherence to ethical behaviour. A self-administered questionnaire was distributed to travellers (n = 228) participating in ecotours to Tambopata Reserve, Peru, who were asked to rate the operators on six dimensions of ethical behaviour. Overall, travellers' perceptions were favourable and strongly related to satisfaction with received service. However, travellers were rarely in a situation nor on-site long enough to observe any questionable practices. The question arises whether the perceptions of travellers are effective indicators of operators' ethical behaviour.